Self‐efficacy, psychological distress, and marital quality in young and middle‐aged couples facing lymphoma: The mediating effect of dyadic coping. Issue 9 (5th May 2021) - An, Huiying; Chen, Changying; Du, Ruofei; Cheng, Chunyan; Wang, Panpan; Dong, Shiqi
Abstract: Objective: This study explored the mediating role of dyadic coping between self‐efficacy, psychological distress and marital quality among young and middle‐aged couples facing lymphoma. Methods: A total of 243 couples in which the patients were lymphoma were recruited to complete Dyadic Coping Inventory, Locke–Wallace Marital Adjustment Scale for both. And Strategies Used by People to Promote Health, Fear of Progression Questionnaire‐Short Form for patients; General Self‐Efficacy Scale and Hospital Anxiety and Depression Scale for spouses. We used the statistical programs SPSS 20.0 and SPSS Amos 20.0 for data analysis. Results: There were significant correlations between patient‐spouse's dyadic coping and marriage quality scores. The patients' dyadic coping scores were significantly associated with their self‐efficacy, fear of cancer recurrence scores, marriage quality, their spouse's self‐efficacy, and marriage quality. The spouses' dyadic coping scores were significantly associated with their self‐efficacy, anxiety, and marriage quality. The actor–partner interdependence mediation model analysis mediator effect of dyadic coping in the relationship between self‐efficacy, psychological distress, and marriage quality had a good fit, with χ 2 / df  = 17.106, p  = 0.194; root mean square error of approximation = 0.036; GFI = 0.992; CN = 243. Conclusions: For both patient and spouses, dyadic coping mediated impact of self‐efficacy on marriage quality of themselves and their spouses, and individuals' dyadic coping mediated impact their psychological distress on marriage quality of themselves and spouses. The study highlighted the need for couple‐based interventions and including strategies combined with individual and dyadic therapy for both partners.